2013
DOI: 10.1111/acps.12172
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of attachment and psychosis: measurement, construct validity and outcomes

Abstract: Objective This review sought to identify, summarise and critically evaluate studies that investigated attachment amongst individuals with psychosis. Method The following computerised databases searched were CINAHL < 1980 to December 2012; EMBASE < 1980 to December 2012; Ovid MEDLINE (R) < 1980 to December 2012; PsychINFO < 1980 to December 2012; and Google Scholar < 1980 to December 2012. Results We identified 22 papers describing 21 studies comprising 1453 participants, with a mean age of 35.0 years (range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
194
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(220 citation statements)
references
References 56 publications
(298 reference statements)
14
194
1
11
Order By: Relevance
“…Exposure to childhood trauma is common among UHR individuals (Kraan et al, 2015a), although evidence linking it to increased risk of transition to psychotic disorder in this group remains inconclusive (Thompson et al, 2014;Kraan et al, 2015b;Stowkowy et al, 2016). Poor engagement with clinical services, more severe psychiatric symptoms and cognitive impairment have all been linked to childhood trauma in patients with psychosis (Aas et al, 2014;Gumley et al, 2014). Post-traumatic stress disorder (PTSD) may also be a comorbid problem among those individuals exposed to trauma, which in turn is associated with poorer employment outcomes even among individuals with serious mental illness (Mueser et al, 2004a;2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to childhood trauma is common among UHR individuals (Kraan et al, 2015a), although evidence linking it to increased risk of transition to psychotic disorder in this group remains inconclusive (Thompson et al, 2014;Kraan et al, 2015b;Stowkowy et al, 2016). Poor engagement with clinical services, more severe psychiatric symptoms and cognitive impairment have all been linked to childhood trauma in patients with psychosis (Aas et al, 2014;Gumley et al, 2014). Post-traumatic stress disorder (PTSD) may also be a comorbid problem among those individuals exposed to trauma, which in turn is associated with poorer employment outcomes even among individuals with serious mental illness (Mueser et al, 2004a;2004b).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that childhood trauma is associated with higher rates of insecure attachment in adulthood among patients with psychosis (Tait et al 2004;Berry et al 2009). Compared with patients with secure attachments, insecure attachment has been associated with worse psychiatric symptoms (Gumley et al 2014) and social cognitive performance (Pos et al 2014). It has also been associated with poorer engagement with clinical services and more interpersonal problems (Gumley et al 2014), including poorer treatment adherence and greater likelihood of disengagement from mental health services (Tait et al 2004;MacBeth et al 2011).…”
Section: Attachmentmentioning
confidence: 99%
“…Compared with patients with secure attachments, insecure attachment has been associated with worse psychiatric symptoms (Gumley et al 2014) and social cognitive performance (Pos et al 2014). It has also been associated with poorer engagement with clinical services and more interpersonal problems (Gumley et al 2014), including poorer treatment adherence and greater likelihood of disengagement from mental health services (Tait et al 2004;MacBeth et al 2011). These may all be important factors that contribute to the association between childhood trauma and poor functioning in these patient groups.…”
Section: Attachmentmentioning
confidence: 99%
“…A large and influential epidemiological study found evidence for an association between insecure adult attachment and schizophrenia (Mickelson et al, 1997), and although this association has been replicated in non-clinical (Berry et al, 2007b;Berry et al, 2006;Korver-Nieberg et al, 2014;Meins et al, 2008) and clinical samples (Berry et al, 2007a;Gumley et al, 2014;Korver-Nieberg et al, 2014;Korver-Nieberg et al, 2015;Ponizovsky et al, 2007;Ponizovsky et al, 2013) it has been suggested that it could be more informative to explore such associations in relation to specific symptoms of psychosis (Bentall, 2004). Such specificities can provide a clearer understanding of how certain psychological mechanism are meaningfully related to the experiences of individuals with psychosis (Bentall and Fernyhough, 2008) and, in turn this information may help clinicians focus psychological interventions appropriately.…”
Section: Introductionmentioning
confidence: 99%